2015
DOI: 10.1523/jneurosci.0457-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Vesicle Release Is Not Tightly Coupled to Voltage-Gated Calcium Channel-Mediated Ca2+ Influx and Is Triggered by a Ca2+ Sensor Other Than Synaptotagmin-2 at the Juvenile Mice Calyx of Held Synapses

Abstract: It is well known that voltage-gated calcium channels (VGCCs)-mediated Ca2ϩ influx triggers evoked synaptic vesicle release. However, the mechanisms of Ca 2ϩ regulation of spontaneous miniature vesicle release (mini) remain poorly understood. Here we show that blocking VGCCs at the juvenile mice (C57BL/6) calyx of Held synapse failed to cause an immediate change in minis. Instead, it resulted in a significant reduction (ϳ40%) of mini frequency several minutes after the blockage. By recording VGCC activity and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…At neocortical excitatory and inhibitory synapses, the dependence of spontaneous release on [Ca 2+ ] o was similarly low ( n = 0.45–0.63) (Groffen et al, ; Vyleta & Smith, ; Williams et al, ). Likewise, at the calyx of Held, a large central synapse, n for spontaneous release is 0.43 (Dai, Chen, Tian, & Sun, ). Overall spontaneous release is [Ca 2+ ] o dependent, albeit with a weaker concentration dependence than evoked release.…”
Section: [Ca2+]o Dependence Of Spontaneous and Evoked Releasementioning
confidence: 99%
See 1 more Smart Citation
“…At neocortical excitatory and inhibitory synapses, the dependence of spontaneous release on [Ca 2+ ] o was similarly low ( n = 0.45–0.63) (Groffen et al, ; Vyleta & Smith, ; Williams et al, ). Likewise, at the calyx of Held, a large central synapse, n for spontaneous release is 0.43 (Dai, Chen, Tian, & Sun, ). Overall spontaneous release is [Ca 2+ ] o dependent, albeit with a weaker concentration dependence than evoked release.…”
Section: [Ca2+]o Dependence Of Spontaneous and Evoked Releasementioning
confidence: 99%
“…While a majority of groups reported that VACCs do not trigger mEPSCs at conventional central synapses in culture and acute brain slices, others report the contrary (Dai et al, ; Ermolyuk et al, ; Xu, Jun, Pang, Ok‐Ho, & Südhof, ). One hypothesis to explain the discrepancy is that Cd 2+ may enter the cell and increase [Ca 2+ ] i via off‐target mechanisms (Ermolyuk et al, ), leading to vesicle depletion so that block of VACCs has no detectable impact on synaptic transmission.…”
Section: Mechanisms Behind Differences In Vacc Regulation Of Spontanementioning
confidence: 99%
“…Many factors regulate the resting intraterminal Ca 2+ ‐concentration which largely contributes to the Ca 2+ ‐dependent minis (Dai et al, ; Ermolyuk et al, ; Pang & Sudhof, ; Sun et al, ; Vyleta & Smith, ). The major contributing factors include the stochastic Ca 2+ ‐channel opening, Ca 2+ release from internal Ca 2+ ‐stores and Ca 2+ ‐sensing receptor (CaSR, a Ca 2+ ‐sensing G‐protein coupled receptors) (Coulombe, Faure, Robin, & Ruat, ; Dai et al, ; Ermolyuk et al, ; Friel & Chiel, ; Lou, Scheuss, & Schneggenburger, ; Pang & Sudhof, ; Sun et al, ; Vyleta & Smith, ). We first observed the divalent cationic influx when extracellular Ca 2+ was switched to Sr 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Single current from VGCCs was recorded in the presence of 1 μM tetrodotoxin (TTX), 20 mM TEA–Cl as described in detail previously (Dai, Chen, Tian, & Sun, ). Changing Ca 2+ ‐concentrations was always balanced by adjusting the concentration of NaCl to keep the osmolarity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation